Comparison of hydrokinetic energy harvesting performance of a fluttering hydrofoil against other Flow-Induced Vibration (FIV) mechanisms. (March 2022) - Tamimi, V.; Wu, J.; Esfehani, M.J.; Zeinoddini, M.; Naeeni, S.T.O.
Abstract: Despite the valuable previous studies on energy harvesting from flutter instability, no decisive ranking still exists between fluttering generators and harvesters based on other Flow-Induced Vibration (FIV) instabilities. In the current empirical study, the hydroelastic response and the energy performance of a self-sustained NACA 0015 hydrofoil are determined and compared to those of oscillators working based on Vortex-Induced Vibration (VIV), galloping, and Wake-Induced Vibration (WIV). Moreover, the effects of an unsteady circular wake on the performance of the hydrofoil are analyzed. With the scale and the aspect ratio considered in the current study, the upstream wake slightly mitigates the FIV response, power, and efficiency of the hydrofoil. Results of the current study show that the three top energy harvesting performances belong to oscillators with instability and combined instability-resonance responses. The high-power production capability of the galloping plus the high efficiency of the VIV makes WIV of the circular oscillator the optimum option for energy harvesting. Specific galloping oscillators like triangular cross-sections can even surpass WIV of the circular oscillator. The average performance of the fluttering hydrofoil makes it the third top instability above all resonance oscillators. Highlights: Top energy performances belong to instability and combined instability-resonance. Small scale unsteady wake doesn't improve the performance of the hydrofoil. Self-sustained hydrofoil surpasses resonance oscillators. Galloping achieves higher power and VIV higher efficiency than other instabilities.